We did it together!. Issue 4 (2nd October 2021) - Bergart, Ann M.
ABSTRACT: The author describes her reluctant entry into the world of online teaching. Like legions of educators, she was thrust into this world by the COVID-19 pandemic. She had to quickly learn a new way to teach social work with groups, bedeviled by the challenge of creating connection and community online. The author briefly describes the first course she taught online, which had limited success. She goes on to discuss the ups and downs of the second course in some detail. There she was able to partner with the students to make necessary adjustments in the way the class was taught. In the end she was confident that the students came away from the course with an experiential understanding of the importance and power of mutual aid.